Workplace Spirituality in State Universities and Colleges: Its Relation to the Work Well-Being and Job Satisfaction of Faculty Members - Noe P. Garcia; Roel D. Juevesa (International Journal of Engineering and Management Research, 2020)
This study determined the relationship of workplace spirituality, work well-being, and job satisfaction among faculty members in state universities and colleges (SUCs) in Region XII, Philippines. The descriptive survey and correlational design were used employing quantitative data. The data were gathered through the questionnaire and administered to the 234 respondents. The gathered data were analyzed through frequency, percentage, weighted mean, and Pearson (r) Coefficient Correlation. The findings of the study revealed that faculty members agreed that their workplace spirituality has a “very high” positive correlation to work well-being (Ho₁). It was also found out that faculty members agreed that their workplace spirituality has a “very high” correlation to job satisfaction (Ho₂). Given the overall results, the study recommends sustaining the workplace spirituality of the faculty members to remain high in their work well-being and job satisfaction.